The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1007/s10681-011-0437-7
|View full text |Cite
|
Sign up to set email alerts
|

Genetic mapping of bph20(t) and bph21(t) loci conferring brown planthopper resistance to Nilaparvata lugens Stål in rice (Oryza sativa L.)

Abstract: Brown planthopper(BPH) is one of the most serious and destructive insect pests of rice in most rice growing regions of the world. In this study, two major resistance genes against BPH have been identified in an Oryza rufipogon (Griff.) introgression rice line, RBPH54. Inheritance of the BPH resistance in RBPH54 was studied by screening the resistance in parents, F1, F2 and BC1 generations against BPH biotype 2. A population of BC3F2 lines was developed and SSR markers were employed for the gene mapping, and ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(16 citation statements)
references
References 33 publications
0
14
0
1
Order By: Relevance
“…Previously, two BPH resistance genes, bph20(t ) and bph21(t ), were identified in RBPH54, a rice introgression line derived from wild rice Oryza rufipogon ( Yang et al , 2011 ). Genetic segregation in the F 2 generation showed a ratio of 1:15, implying that the resistance was governed by recessive alleles at two loci.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, two BPH resistance genes, bph20(t ) and bph21(t ), were identified in RBPH54, a rice introgression line derived from wild rice Oryza rufipogon ( Yang et al , 2011 ). Genetic segregation in the F 2 generation showed a ratio of 1:15, implying that the resistance was governed by recessive alleles at two loci.…”
Section: Introductionmentioning
confidence: 99%
“…To date, some BPH resistance genes and a BPH quantitative resistance locus (QRL) have been found on the short arm of rice chromosome 616: Bph3 3334, bph4 56, BPH25 10 ( bph20(t )15) and qBPH(t )57. The rice variety Ptb33 showed a higher degree and a broader spectrum of BPH resistance than has been described previously24293358.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the BPH resistance genes Bph1 and bph2 rapidly became obsolete in just 3–5 years because of the development of new BPH biotypes7. Since the first reports of the BPH resistance genes Bph1 and bph2 by Athwal et al 8, at least 30 new BPH resistance loci have been identified from cultivated and wild species of Oryza 79101112131415161718. To date, four of these resistance genes, Bph14 19, BPH26 11, Bph3 20 and BPH29 12, have been cloned.…”
mentioning
confidence: 99%
“…Bph1 and bph2 were the first two resistance genes screened via a rice breeding program at the International Rice Research Institute (IRRI). To date, 28 N. lugens resistance genes (designated BPH1-28) have been identified, and most have been mapped to rice chromosomes in cultivated and wild rice species (Kabir and Khush 1988;Nemoto et al 1989;Kawaguchi et al 2001;Liu et al 2001;Murai et al 2001;Renganayaki et al 2002;Sharma et al 2004;Yang et al 2004;Kim and Sohn 2005;Chen et al 2006;Jena et al 2006;Sun et al 2006;Rahman et al 2009;Qiu et al 2010;Yara et al 2010;Hu et al 2012;Myint et al 2012;Yang et al 2012;Cheng et al 2013;Daisuke et al 2013;He et al 2013;Tamura et al 2014;Wu et al 2014). These genes confer resistance by inhibiting N. lugens sucking from rice phloem, and reducing growth and survival rates of N. lugens population, or confer resistance via N. lugens tolerance behavior, e.g., Bph28 (Cheng et al 2013;Wu et al 2014).…”
Section: Interaction Of N Lugens and Rice Plantmentioning
confidence: 99%